Analysis of the Implementation of Sim Bphtb Application in West Lombok as One of the Digitalization Accelerations in BPHTB Collection - Anindya, Baiq Ailsa; Lestari, Baiq Anggun Hilendri; Ridhawati, Rini (International Journal of Business and Applied Economics, 2024)
The Acquisition Duty on Land and Building (BPHTB) collection in West Lombok Regency is now digitized using the BPHTB Management Information System (SIM BPHTB) application. This research uses a qualitative descriptive approach to analyze the implementation of the SIM BPHTB application at the BAPENDA Office of West Lombok Regency. Data was collected by conducting semi-structured interviews that were related to SIM BPHTB. The results of this study indicate that SIM BPHTB can make BPHTB collection more effective and efficient, as the processing of BPHTB documents is faster and does not require a large workforce. Furthermore, it provides transparency, as BPHTB payments can be made through EDC machines or banks, allowing real-time monitoring. SIM BPHTB also enhances Local Own-Source Revenue (PAD), as using this application enables more BPHTB documents to be processed, resulting in increased revenue.